OP0186 Etiological therapy in HCV-related mixed cryoglobulinemia syndrome: The role of IL28B genotype as predictor of response. (23rd January 2014) - Urraro, T.; Piluso, A.; Giannini, C.; Fognani, E.; Gragnani, L.; Caini, P.; Monti, M.; Triboli, E.; Pellegrini, E.; Petrarca, A.; Ranieri, J.; Laffi, G.; et al.
Abstract : Background: Mixed cryoglobulinemia syndrome (MCS) is a HCV-related, invalidating lymphoproliferative disorder (LPD) whose manifestations are related to a systemic vasculitis. The pathogenesis of MCS is a multistep process involving a strong and sustained B-cell proliferation and genetic events on the basis of host predisposing factors [1]. Standard of care (SOC: PegIFN+RBV) anti-HCV therapy is now the first therapeutic option in HCV+ MCS, however, due to its side effects, the therapeutic decision is often difficult, especially in MCS patients with HCV-G1/4 [2]. Consequently, the possibility to better predict the therapy outcome would be precious. In hepatitis C, genetic variations in the IL28B gene, are strongly associated with the response to anti-HCV therapy [3]. Nowadays, IL28B polymorphisms in HCV-related MCS has been never investigated and it is not possible to exclude that the complex modifications of the immune system characterizing MCS could modify its predictive value. Objectives: The aim of this study was to evaluate the role of IL28B genotype in influencing the response to IFN-based treatment and in predisposing to MCS. Methods: The IL28B polymorphism was investigated by using allele-specific real-time PCR tecniques in 515 HCV-positive patients: 267 with MCS and 248 without MCS or any LPD (controls). Results: A comparable distribution of the IL28B alleles (rs12979860/rs8099917) for HCV-positive patients with and without MCS was recorded, suggesting that this polymorphism do not play a major role in conditioning MCS evolution. Among the 267 HCV-MCS, 123 patients completed a SOC anti-HCV treatment and at least 24 weeks of follow-up. A significant correlation between IL28B major allele homozygosis and MCS response was observed (p=0.0021); the clinical response almost coincided with the virological one. The logistic regression analysis defined the IL28B genotype as a strong independent predictor of MCS response (p=0.0069, odds ratio 6.11; C.I. 1.58-21.22). According to HCV genotype, the predictive value was limited to the most frequent and difficult-to-treat HCV genotypes. Conclusions: For the first time, we showed that in HCV-G1/4-MCS patients, IL28B genotype is an useful predictor of response to IFN-based therapy. This would greatly help in the management of this difficult category of HCV patients. This study also suggests that IL28B genotype do not influence the evolution of HCV infection to MCS References: Zignego AL, Giannini C, Ferri C: Hepatitis C virus-related lymphoproliferative disorders: an overview. World J Gastroenterol 2007, 13:2467-2478. EASL Clinical Practice Guidelines: management of hepatitis C virus infection. J Hepatol 2011, 55:245-264. Ge D, Fellay J, Thompson AJ, Simon JS, Shianna KV, Urban TJ, et al. Genetic variation in IL28B predicts hepatitis C treatment-induced viral clearance. Nature 2009; 461:399-401 Disclosure of Interest: None Declared